2021
DOI: 10.17973/mmsj.2021_03_2020068
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Accuracy of Virtual Clamping in the Field of 3d Scanning

Abstract: When measuring large and flexible parts, specialised measuring and clamping jigs are used as the standard, which fix the part to the required position. However, because the production of such jigs is time consuming and very expensive, software tools have recently started to appear on the market, which allow even large flexible parts to be measured in a free state and to use so-called virtual clamping for alignment the part in the mounting position. This technique uses the finite element method to simulate defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…If the surface does not have a matte finish, the obtained result can be distorted, often by a as much as one tenth of a millimeter [10]. They also investigated another important parameter of optical 3D scanning, which is clamping that can influence the results mainly in the case of measuring large and flexible parts [11]. It was found that the use of titanium powder is most suitable for measuring objects with high precision [12].…”
Section: Introductionmentioning
confidence: 99%
“…If the surface does not have a matte finish, the obtained result can be distorted, often by a as much as one tenth of a millimeter [10]. They also investigated another important parameter of optical 3D scanning, which is clamping that can influence the results mainly in the case of measuring large and flexible parts [11]. It was found that the use of titanium powder is most suitable for measuring objects with high precision [12].…”
Section: Introductionmentioning
confidence: 99%